Rancang Bangun Permainan Arkade Aksara Sunda Menggunakan Metode Game Development Life Cycle - Ilyasa, Salya; Fitriani, Leni (Institut Teknologi Garut, 2025)
This research aims to develop an arcade game based on Sundanese script as an interactive educational media. The main contribution of this research is the systematic application of the Game Development Life Cycle (GDLC) method in the development of educational games, as well as testing their effectiveness in improving the understanding of Sundanese script among elementary school students. The GDLC method was used to ensure that the development of the game was carried out in stages from initiation to release. The results showed that the game developed was able to increase students' interest and understanding of Sundanese script, as evidenced through Alpha Testing and Beta Testing evaluations. Compared to previous studies, this approach focuses more on the entertainment and interactivity aspects of Sundanese script learning. Thus, this research contributes to the development of more interesting and effective game-based learning media.